Reduction in final year medical students’ knowledge during the COVID-19 pandemic: Insights from an interinstitutional progress test - Hamamoto Filho, Pedro Tadao [UNESP]; Cecilio-Fernandes, Dario; Norcia, Luiz Fernando [UNESP]; Sandars, John; Anderson, M. Brownell; Bicudo, Angélica Maria (Frontiers, 2022)
There has been little information about how the COVID-19 pandemic has impacted medical students’ knowledge acquisition. The aim of the study was to identify the impact of the COVID-19 pandemic on medical students’ knowledge acquisition by comparing the students’ performance on two Progress Test exams administered in 2019 (pre-pandemic) and 2020 (during the pandemic). We included data from 1,491 students at two medical schools in Brazil. Both schools had experienced interrupted preclinical classes and clinical clerkship rotations in March 2020 but had resumed remote preclinical classes with online activities within 1 month after the interruption and clerkship rotations within five to 6 months after the interruption. We analyzed the data with the Rasch model from Item Response Theory to calibrate the difficulty of the two exams and calculated the performance of the students, with comparison of the differences of mean knowledge for each year and between the two cohorts. We found that the students’ knowledge in the cohort of 2019 was higher than those in the cohort of 2020, except in the second year. Also, the students did not show any increase in knowledge between 2019 and 2020 in the clerkship years. It appears that the pandemic significantly impaired the knowledge acquisition of medical students, mainly in the clerkship years, where practical activities are the central part of training. This is of special concern in low- and middle-income countries where graduated medical doctors are allowed to practice without further training or are required to have continuing professional development.
Keywords: assessment; COVID-19; knowledge acquisition; medical education; progress testing